A love song for Ricki Wilde : a novel [large type] - Williams, Tia, 1975- (Grand Central Publishing, 2024)
"Leap years are a strange, enchanted time. And for some, even a single February can be life-changing. Ricki Wilde has many talents, but being a Wilde isn't one of them. As the impulsive, artistic daughter of a powerful Atlanta dynasty, she's the opposite of her famous socialite sisters. Where they're long-stemmed roses, she's a dandelion: an adorable bloom that's actually a weed, born to float wherever the wind blows. In her bones, Ricki knows that somewhere, a different, more exciting life awaits her. When regal nonagenarian, Ms. Della, invites her to rent the bottom floor of her Harlem brownstone, Ricki jumps at the chance for a fresh beginning. She leaves behind her family, wealth, and chaotic romantic decisions to realize her dream of opening a flower shop. And just beneath the surface of her new neighborhood, the music, stories and dazzling drama of the Harlem Renaissance still simmer. One evening in February as the heady, curiously off-season scent of night-blooming jasmine fills the air, Ricki encounters a handsome, deeply mysterious stranger who knocks her world off balance in the most unexpected way. Set against the backdrop of modern Harlem and Renaissance glamour, A Love Song for Ricki Wilde is a swoon-worthy love story of two passionate artists drawn to the magic, romance, and opportunity of New York, and whose lives are uniquely and irreversibly linked"--